Analisis Efektivitas Mesin Injection Moulding pada Lantai Produksi Menggunakan Metode Overall Equipment Effectiveness (OEE) - Riana Magdalena Silitonga; Maria Magdalena Wahyuni Inderawati; Agustinus Silalahi (Metris: Jurnal Sains dan Teknologi, 2026)
The plastic manufacturing industry operating under a make-to-order system demands a high level of efficiency and effectiveness in the operation of production equipment to meet demand targets. Production processes that utilize injection molding machines with high utilization rates and a two-shift work system have the potential to generate various problems that can negatively affect production performance. Therefore, measuring machine effectiveness is necessary to identify factors contributing to performance deterioration. This study aims to measure the level of machine effectiveness using the Overall Equipment Effectiveness (OEE) method and to identify the dominant problems through Pareto diagram analysis. The research employs a quantitative approach, with data collection consisting of operating time, downtime, and production output. The results indicate that the OEE value is 69%, which is still below the industry standard of 80%. The primary issue influencing the low OEE value is the high frequency of idling and minor stoppages, which leads to significant losses in production time. Consequently, focused improvement efforts are required to enhance machine effectiveness and achieve sustainable improvements in production performance.